Sorting device for duck egg processing - ZHA ANCHUN; LIANG YONG; ZHU WANJING; YIN HENGBING; ZHANG WANLIN; CHEN JING (2024)
The utility model discloses a sorting device for duck egg processing, and relates to the technical field of duck egg processing. The sorting platform is inclined; the two ends of the outer wall of the sorting platform are fixedly connected with a feed opening and a discharge opening correspondingly. Supporting columns are fixedly connected to the bottom ends of the outer walls of the sorting platform and the discharging opening; the duck eggs can be repeatedly cleaned and wiped by the sponge layer on the outer side wall of the rotating shaft when sliding downwards, and then are washed by the cleaning brush on the rotating roller for several times, so that the outer surfaces of the duck eggs are cleaned, and when the duck eggs reach the discharge port, the qualified duck eggs touch the sorting plate and slide to the other side of the bevel edge along the bevel surface of the sorting plate; when the duck eggs are not qualified, the duck eggs can directly penetrate through the gap between the sorting plate and t